Memories and reflections - Siriwardene, P. P. G. L., 1925- (Ratmalana : Vishva Lekha, 2000)
Autobiographical account of a former professor and later vice-chancellor of Colombo University.
Keywords: Siriwardene, P. P. G. L., -- 1925-; College teachers -- Sri Lanka -- Biography